The Frequency of Bk Polyomavirus Viruria in A Sample of Iraqi Children with Acute Lymphoblastic Leukemia (Iraqi Journal of Medical Sciences, 2025)
Background: BK Polyoma virus (BKPyV) is a ubiquitous virus and infect children at early age and becomes latent and it has been found as the main cause of hemorrhagic cystitis in hematopoietic stem cell transplantation patients, due to immunosuppression regimen that led to the activation of the virus from the latency status and lead to increased viral shedding in urine. Objective: To find the frequency of BKPyV-DNA in urine (viruria) among acute lymphoblastic leukemia (ALL) patients as compared to healthy controls and compare it with age, sex, relapse and leukocytes level.Methods: Urine samples were collected from 60 ALL patients, and 60 apparently healthy age and sex-matched children who were taken as a control group. The BKPyV-DNA in urine (viruria) was detected using real time polymerase chain reaction and Pap-stained urine cytology smears were checked to identify the presence of decoy cells (DCs).Results: The BKPyV-DNA was detected in the urine of all patients (100.0%) and in 55.0% of control group (P <0.001) and all the patients were DCs negative. There was no significant effect of the positivity of viruria on neither leukocytes level nor on the occurrence of relapse in leukemia patients.Conclusion: The very high frequency of BKPyV-DNA in urine (viruria) indicates the importance of reactivation of this virus in ALL patients with and without chemotherapy.Keywords: Acute lymphoblastic leukemia, BK Polyoma virus, real time-PCR.Citation: Ali SH, Abbas SS, Ali AH, Al-Obaidi AB. The frequency of Bk polyomavirus viruria in a sample of Iraqi children with acute lymphoblastic leukemia. Iraqi JMS. 2025; 23(1): 119-127. doi: 10.22578/IJMS.23.1.14